2002
DOI: 10.1093/carcin/23.6.1009
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of sinigrin (2-propenyl glucosinolate) by the human colonic microflora in a dynamic in vitro large-intestinal model

Abstract: Cruciferous vegetables, such as Brassica, which contain substantial quantities of glucosinolates, have been suggested to possess anticarcinogenic activity. Cutting and chewing of cruciferous vegetables releases the thioglucosidase enzyme myrosinase, which degrades glucosinolates to isothiocyanates and other minor metabolites. Cooking of cruciferous vegetables inactivates the myrosinase enzyme, allowing intact glucosinolates to reach the large intestine, where they can be degraded by the indigenous microflora i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
77
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(84 citation statements)
references
References 37 publications
6
77
0
1
Order By: Relevance
“…They showed that the bioavailability of isothiocyanates from fresh broccoli is approximately three times higher than that from steamed broccoli, in which myrosinase is inactivated. The microbial gut flora is also capable of forming isothiocyanates but the efficiency is lower compared to the action of plant myrosinase [272]. Food products containing active myrosinase, like sprouting Brassica vegetables and shortly cooked Brassica vegetables are preferred.…”
Section: Myrosinase Activitymentioning
confidence: 99%
“…They showed that the bioavailability of isothiocyanates from fresh broccoli is approximately three times higher than that from steamed broccoli, in which myrosinase is inactivated. The microbial gut flora is also capable of forming isothiocyanates but the efficiency is lower compared to the action of plant myrosinase [272]. Food products containing active myrosinase, like sprouting Brassica vegetables and shortly cooked Brassica vegetables are preferred.…”
Section: Myrosinase Activitymentioning
confidence: 99%
“…The processes of ingestion and digestion of brassica vegetables lead, therefore, to glucosinolate hydrolysis. Myrosinase activity has also been demonstrated in the human gut microflora (3,4). Glucosinolate hydrolysis can lead to a range of breakdown products, depending on the conditions under which hydrolysis occurs and the structure of the parent glucosinolate.…”
Section: Introductionmentioning
confidence: 99%
“…AITC is derived from its precursor sinigrin (a glucosinolate) following myrosinase-catalysed hydrolysis (Krul et al 2002;Bhattacharya et al 2010). AITC directly interacts with sulfhydryl groups (Zhang et al 2005) and predominantly conjugates with cysteine residues .…”
Section: Introductionmentioning
confidence: 99%